ENHANCING STUDENTS' ATTITUDE AND ACHIEVEMENT IN BIOLOGY THROUGH INNOVATIVE STRATEGIES - Njoku, Martha Ijok Adibe; Nwagbo, Chinwe Rose (PEOPLE: International Journal of Social Sciences, 2020)
In this research, the impact of peer tutoring and group tutoring led to team learning approaches on the attitude of the students towards and achievement in biology. The thesis had been motivated by four research questions and six null hypotheses. The research had used a quasi-experimental method. In particular, the design of the un-equivalent control group. The sample size was 182 SS 1 students from the four sampled government senior high schools in Port-Harcourt metropolis, River State, Nigeria in four intact classrooms. Two of the classes were exposed to peer tutoring while the remaining two were exposed to peer-led team learning strategies. Biology Attitudinal Scale (BAS), and Biology Achievement Test (BAT) were data collection instruments. BAS construct validity was developed using factor analysis, while BAT material validity was calculated using the specification table. Reliability for BAS and BAT was obtained using formula 20 (K-R 20) from Cronbach Alpha and Kudar-Richardson. Mean and the standard deviation was used to answer the study questions while Covariance analysis (ANCOVA) was used to evaluate the hypotheses at 0.05 significance point. The findings showed that peer-led team learning approach is better than peer tutoring in enhancing the attitude and achievement of the students in biology. The implications of the findings were highlighted and recommendations made.